Resting-State Oscillatory Activity in Children Born Small for Gestational Age: An MEG Study - Boersma, Maria; de Bie, Brigitte; Oostrom, Kim; van Dijk, Bob; Hillebrand, Arjan; Van Wijk, Bernadette; Delemarre-van de Waal, Henriette; Stam, Cornelis Jan (Frontiers in Human Neuroscience, 2013)
Growth restriction in utero during a period that is critical for normal growth of the brain, has previously been associated with deviations in cognitive abilities and brain anatomical and functional changes. We measured magnetoencephalography (MEG) in 4-7 year old children to test if children born small for gestational age (SGA) show deviations in resting-state brain oscillatory activity. Children born SGA children with postnatally spontaneous catch-up growth (SGA+; 6 boys, 7 girls; mean age 6.3 y (SD=0.9) and children born appropriate for gestational age (AGA; 7 boys, 3 girls; mean age 6.0 y (SD=1.2) participated in a resting-state MEG study. We calculated absolute and relative power spectra and used nonparametric statistics to test for group differences. SGA+ and AGA born children showed no significant differences in absolute and relative power except for reduced absolute gamma band power in SGA children. At time of MEG investigation, SGA+ children showed was significantly lower head circumference (HC) and a trend toward lower IQ, however there was no association of HC or IQ with absolute or relative power. Except for reduced absolute gamma band power, our findings suggest normal brain activity patterns at school age in a group of children born SGA in which spontaneous catch-up growth of bodily length after birth occurred. Although previous findings suggest that being born SGA alters brain oscillatory activity early in neonatal life, we show that these neonatal alterations do not persist at early school age when spontaneous postnatal catch-up growth occurs after birth.